Application of H∞-optimal controllers for battery-based bidirectional DC/DC converters in hybrid energy storage systems - Jianwen Meng; Qihao Guo; Jianheng Lin; Meiling Yue; Demba Diallo (International Journal of Electrical Power & Energy Systems, 2024)
Lithium-ion battery-based hybrid energy storage systems (ESSs) have been widely applied in various fields. Bidirectional DC/DC converters, crucial interfaces linking batteries and DC buses, serve as critical actuators for tasks such as DC bus regulation, on-line battery diagnosis, health-conscious energy management strategy, and fault tolerant control. Despite their importance, the control of bidirectional DC/DC converters in hybrid ESSs has rarely been independently discussed. Their control-related works are usually carried out by the unidirectional DC/DC converter modeling process with proportional–integral (PI)-type controllers. Therefore, recognizing the significance of pulsed power loads and the induced highly dynamic changes in battery voltage during real-world applications, this paper highlights the relevance of applying H∞-optimal controllers for bidirectional DC/DC converters based on its detailed control-oriented modeling process. To present a rigorous H∞-optimal controller synthesis process, this study includes a detailed experimental determination of the controller’s key parameters. Furthermore, extensive numerical tests across diverse battery operation scenarios have been conducted to demonstrate the advantages of applying H∞-optimal controllers for battery-based bidirectional DC/DC converters in hybrid ESSs.